2015
DOI: 10.4236/aces.2015.52023
|View full text |Cite
|
Sign up to set email alerts
|

<i>N</i>-Acetylated Gemini Surfactants: Synthesis, Surface-Active Properties, Antifungal Activity, and Ecotoxicity Bioassays

Abstract: A series of N-acetylated cationic gemini surfactants (3a-e) having dimeric structures derived from tertiary amines were synthesized. Their antifungal potency and surface properties were determined. It also studied the acute toxicity of the molecule with the best performance and the best water solubility (3e) through Chlorella vulgaris and Daphnia magna bioassays. The results were compared to those obtained for a commercially available reference compound 2-(thiocyanomethylthio) benzothiazole (TCMTB). Parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The characterization of gemini bilayer properties is additionally essential for the many proposed biological applications of these surfactants. Gemini surfactants have received considerable interest for applications as antimicrobials, and as liposome constituents for both drug delivery and DNA transfection; in these applications, the surfactant/lipid bilayer interaction is of primary importance. Several mechanistic studies of the interaction between geminis and lipid membranes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization of gemini bilayer properties is additionally essential for the many proposed biological applications of these surfactants. Gemini surfactants have received considerable interest for applications as antimicrobials, and as liposome constituents for both drug delivery and DNA transfection; in these applications, the surfactant/lipid bilayer interaction is of primary importance. Several mechanistic studies of the interaction between geminis and lipid membranes have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Inoculum concentration was verified by spread plate method. All macrodilution tests were incubated for 48-72 h to determine MIC (Machuca & Murguía, 2020;Machuca et al, 2015). All the tests included drug-free and fungifree controls.…”
Section: Susceptibility Testsmentioning
confidence: 99%
“…From an ecological point of view, the functionalization of substituents with groups of natural origin is of great importance, because it can increase their biological profile, improving biodegradability or reducing ecotoxicity [ 8 , 38 ]. Gemini surfactants are referred to as multifunctional, because one compound may be an exceptionally effective surface active agent [ 39 , 40 , 41 ], corrosion and biocorrosion inhibitor [ 42 , 43 , 44 , 45 , 46 , 47 ], but also has remarkably high antibacterial [ 48 , 49 , 50 , 51 ] and antifungal [ 52 , 53 , 54 , 55 , 56 , 57 ] activity and is effective in preventing biofilm eradication [ 52 , 58 ]. It is worth emphasizing that gemini surfactants work effectively at a very low concentration, often several times smaller in comparison to single quaternary ammonium salts [ 59 , 60 , 61 , 62 , 63 ].…”
Section: Introductionmentioning
confidence: 99%